Freqüência de amostragem de plantas de alface hidropônica para ajuste de curvas de crescimento - Santos, Paula Machado dos (2006)
In order to construct growth curves is necessary a sequence of many samples taken during lettuce growth period. However, mainly when the trial is made in a controlled environment, sampling frequency is limited. This work was carried out with the aim to reduce sampling destruction effect without change the result precision. Two field trials were made in a controlled environment, during two season, spring (09/20/2004 a 01/12/2005) and autumn (02/27/2005 a 07/20/2005), in the UFSM experimental area, Santa Maria, RS. Different sampling frequencies were simulated, using the adjust of diary sampling model. Optimum sampling frequency was made by comparing daily sampling model with simulated sampling model, in twos, by F test (p<0,005), using the error mean square of non linear regression analysis, pondered by freedom degrees. Simulations of the following variables: total, foliar, root and foliar area phytomass, were made just considering vegetative period and complete growth period. The result shows that season and period of growth should be taken into account to establish the best sampling frequency. Trials conducted during spring season, with complete growth period, show best results with samples taken in intervals of 3 (total), 8 (foliar), 20 (roots) and 9 (foliar area) days; with vegetative period, samples should be taken in intervals of 2,2,4 and 1 days. Trials conducted during autumn season, with complete growthperiod, the sample frequency should be of 2, 11, 12 and 11 days; and for vegetative growth, should be 2, 3, 4 and 1 days